An audit of urological MDT decision making in the South West of England. (July 2018) - Hounsome, Luke; Verne, Julia; Persad, Raj; Bahl, Amit; Gillatt, David; Oxley, Jon; Macdonagh, Ru; Graham, John; Pocock, Richard
Objective: The formation of multidisciplinary teams (MDTs) was formalised for urological cancer services by the National Institute for Health and Care Excellence (NICE) in the 2002 Improving Outcomes in Urological Cancer guidance. This project aimed to assess the variability of MDT recommendations when presented with the same patient. It covered the type and grade of tumour, recorded stage, treatment recommendations and whether clinical trials were considered. Materials and methods: Anonymised details of 10 patients were sent to South West Trust MDTs in two tranches. Details included age, clinical history, haematology and biochemistry results, digital radiology, and pathology text. A panel of representative urologists and urological oncologists from the region decided on optimal treatment and key points of management decisions. Results: The MDTs were not consistent in decision making. This agrees with a previous survey of urologists which also showed inconsistent decision making, and under-use of clinical cues. Some decisions contradicted NICE guidelines in force at the time. Conclusions: MDTs are now an instrumental, integrated part of cancer management. It is vital for assurance of best patient care and best outcomes that the MDT considering and planning treatment is fully functional and well informed on the evidence base, with effective communications. This audit suggests that this is not the case. The Oxford Centre for Evidence-based Medicine – Levels of Evidence is not applicable to this study.